Pengembangan Kawasan Cagar Budaya Bukit Tutari dengan Konsep Ekowisata Berkelanjutan Berbasis Masyarakat Adat : Studi Kasus : Kampung Doyo Lama, Distrik Waibu - Meicelin Apaseray; Elisabeth Veronika Wambrauw; James Modouw (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The Bukit Tutari Cultural Heritage Area in Jayapura Regency, Papua, has enormous potential to be developed as a sustainable ecotourism destination. This study aims to explore strategies for developing the area by involving indigenous people as the main managers. Through a community- based approach, it is hoped that this development will not only improve local economic welfare, but also preserve cultural and environmental values. This study uses a qualitative method with data analysis from interviews, observations, and literature studies. The results of the study indicate that the involvement of indigenous people in ecotourism management can create synergy between cultural preservation and local economic development.